Business Model Canvas : ‘Dryon Machine’ / Nor Syafiqah Azwani Rosly - Rosly, Nor Syafiqah Azwani (2020)
This Business Model Canvas is designed to guide thinking through each of the key components or building blocks for devising our Dryon Machine. Dryon Machine is an automatic ironing machine that has three modes which is dry, steam and iron. The special features of this Dryon Machine is this machine equipped with an automatic adjustable garment rack. Dryon Machine helps user to save their time and energy from doing the ironing task. Business Model Canvas for Dryon Machine is important because it allows us to understand how each aspect relates to the others, how the functions, activities and processes interlink and interlock. It gets us to think about our business in a more systematic and formal way, ensuring that each area is effectively covered to produce a more comprehensive and considered picture of the business. The BMC focusses the business on the strategic elements that matter most and will have the greatest impact on driving growth. It is visual nature aids comprehension by being able to see the overall picture of the business and thereby spot areas of strength and weakness depending on the inputs. It builds the business model such that the whole is comprised of and greater than the sum of the parts